(untitled) (Hà Nội, 2014)
Conten: Overview of rice post harvest situation in the world and in Viet Nam; Paddy harvesting; Paddy drying; Paddy storage; Rice milling; Paddy rice quality; Paddy seed quality; Laser controlled land leveling; Economic calculations for postharvest machinery; Business models and business plans
Keywords: Rice,Rice,Lúa,Lúa; Postharvest technology,Postharvest technology,Công nghệ sau thu hoạch,Công nghệ sau thu hoạch; Vietnam,Việt Nam